Incorporation of oXiris Bioabsorbent Filter into CRRT in the treatment of severe abdominal infections and analysis of associated risk factors for early off-machine - Dong, Yanfang; Chen, Jieling; Zhang, Xiaoli; Wu, Shiyu; Li, Yiming; Zhang, Qiaoxian (Frontiers in Public Health, 2025)
IntroductionThis study aims to evaluate the impact of oXiris continuous renal-replacement therapy (CRRT) on the prognosis of patients with severe intra-abdominal infections (IAIs) and to analyze potential risk factors for early off-machine of oXiris CRRT during treatment.MethodsA total of 49 patients with severe abdominal infections admitted to the intensive care unit of the First Affiliated Hospital of Fujian Medical University from October 2020 to October 2023 were retrospectively analyzed. The patients were divided into a conventional group and an oXiris group. Heart rate, blood lactate level, mean arterial pressure, and total CRRT operation time were observed 72 h before and after CCRT treatment.ResultsWhen comparing changes in indicators over the 72-h period between the two groups, no significant difference in survival rate was observed between the two groups. D-dimer [per 1 ng/mL increase, odds ratio (OR) = 0.930, 95% confidence interval (CI): 0.866–0.999] was identified as a risk factor for early off-machine. In contrast, prothrombin time (PT, per 1-s increase, OR = 1.117, 95% CI: 1.017–1.226), activated partial thromboplastin time (APTT, per 1-s increase, OR = 1.021, 95% CI: 1.006–1.037), and blood flow velocity (per 1 mL/min increase, OR = 1.027, 95% CI: 1.009–1.046) were found to be protective factors.ConclusionoXiris CRRT is associated with a better prognosis in the treatment of severe abdominal infections. APTT, PT, D-dimer, and blood flow velocity are associated with early off-machine during oXiris CRRT.